2022
DOI: 10.1002/jcop.22934
|View full text |Cite
|
Sign up to set email alerts
|

Associations between HIV stigma, gender, and depression among people living with HIV in Hyderabad, India

Abstract: The goal of this study was to explore the association between HIV stigma and depression and whether gender moderated this relationship. The theoretical framework for the study combined an adapted version of Goffman's conceptualization of stigma with gender role theory. We surveyed 150 individuals living with HIV in Hyderabad, India (51 cisgender women, 49 cisgender men, and 50 third gender people) on their experiences with HIV stigma. While third gender people had statistically higher scores for HIV stigma ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 65 publications
1
8
0
Order By: Relevance
“…Eligibility criteria for study inclusion were that respondents were: (a) residing in Hyderabad or Secunderabad, India; (b) living with HIV; (c) proficient in speaking Telugu or Hindi/Urdu; (d) identified as cisgender women or third gender; (e) between the ages of 18 and 50 years old. 73 The initial study consisted of two phases. Phase one had a total of 150 survey respondents who were living with HIV, including 51 cisgender women, 50 cisgender men, and 50 third gender people.…”
Section: Samplementioning
confidence: 99%
See 3 more Smart Citations
“…Eligibility criteria for study inclusion were that respondents were: (a) residing in Hyderabad or Secunderabad, India; (b) living with HIV; (c) proficient in speaking Telugu or Hindi/Urdu; (d) identified as cisgender women or third gender; (e) between the ages of 18 and 50 years old. 73 The initial study consisted of two phases. Phase one had a total of 150 survey respondents who were living with HIV, including 51 cisgender women, 50 cisgender men, and 50 third gender people.…”
Section: Samplementioning
confidence: 99%
“…Cisgender women and third gender respondents were then stratified by their response scores on Berger's HIV Stigma Scale. 73,75 Two subpopulations were then created for each gender identity. This narrowed the respondents to include experiences of eight cisgender respondents with the highest rates of HIV stigma and eight cisgender respondents with the lowest rate of stigma for a total of 16 cisgender women respondents.…”
Section: Samplementioning
confidence: 99%
See 2 more Smart Citations
“…Many studies have reported that stigma and discrimination occur within one's family, such as siblings, relatives, and even parents. This often results from the fear of HIV transmission and remains a persistent global challenge in reducing infection rates [11,[15][16][17]. The fear of contracting HIV occurs from a lack of knowledge about HIV and is a driving factor for stigma and discrimination against people living with HIV [14,18,19].…”
Section: Introductionmentioning
confidence: 99%